Thermally conductive sheet and method for manufacturing electronic device using the same
By introducing crosslinking agent into the thermal conductor and aligning the scale-like filler, the thermal conductivity and durability problems of the thermal conductor between the heat generating element and the heat radiator are solved, and the high thermal conductivity and durability of the electronic device are achieved.
Patent Information
- Application Number
- JP2023123747
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-07
AI Technical Summary
In the prior art, in electronic devices, the durability and thermal conductivity of the thermal conductivity of the thermal conductivity are insufficient, especially under pressure changes between the heat generating element and the heat radiator, the thermal conductivity and durability of the thermal conductivity of the thermal conductivity are difficult to maintain.
Using a thermal conductive sheet containing a flake-like filler, at least part of the resin is crosslinked by introducing a crosslinking agent into the thermal conductive sheet, and the flake-like filler is arranged in an angle of 60° to 90°. The thermal conductive sheet is heated and pressed between the heat generating element and the heat radiator to form chemical bonds and enhance adhesion.
The thermal conductivity and durability of the electronic device are improved, and good contact and bonding can be maintained between the heat generating element and the heat radiator, adapting to the pressure changes caused by thermal expansion and contraction.
Smart Images

Figure 2025019873000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermally conductive sheet and a method for manufacturing an electronic device using the same. [Background technology]
[0002] In recent years, the amount of heat generated by electronic components such as power semiconductors (e.g., IGBT modules) and integrated circuit (IC) chips has increased as their performance has improved. As a result, it has become necessary to take measures to prevent functional failures caused by temperature increases in electronic devices that use these components.
[0003] As a countermeasure against functional failures caused by temperature rises in electronic components, a method is generally adopted in which a heat sink, heat sink plate, heat sink fin, or other heat sink made of metal is attached to the heat generating body of the electronic component to promote heat dissipation. When using a heat sink, in order to efficiently transfer heat from the heat generating body to the heat sink, a sheet-like member with high thermal conductivity (thermal conductive sheet) is placed between the heat generating body and the heat sink, and a certain pressure is applied to the thermal conductive sheet to bring the heat generating body and the heat sink into close contact with each other.
[0004] For example, Patent Document 1 discloses a method for manufacturing a semiconductor device, which includes a step of applying pressure in the thickness direction of a thermally conductive sheet between a heating element and a heat sink, the heating element and the heat sink being arranged with the thermally conductive sheet having a compressive elastic modulus and a tack strength each within a predetermined range, to bond the heating element and the heat sink via the thermally conductive sheet. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2018-203857 A Summary of the Invention [Problem to be solved by the invention]
[0006] Here, when using an electronic device having a thermally conductive sheet interposed between a heating element and a heat sink, not only is the thermally conductive sheet exposed to high temperatures due to the heating element generating heat during operation, but also the expansion of components such as the heating element and heat sink at such high temperatures may apply pressure to the thermally conductive sheet. Then, when the electronic device stops operating, the components cool and contract, which may relieve the pressure. Therefore, an electronic device having a thermally conductive sheet interposed between a heating element and a heat sink is required to maintain good thermal conductivity even when exposed to changes in pressure conditions caused by the expansion and contraction of the components, in other words, to have excellent durability of thermal conductivity.
[0007] However, the above-mentioned conventional techniques leave room for improvement in terms of durability of thermal conductivity in electronic devices.
[0008] Therefore, an object of the present invention is to provide an electronic device having excellent durability in thermal conductivity. [Means for solving the problem]
[0009] The present inventors have conducted extensive research to achieve the above object. The present inventors have newly discovered that, when manufacturing an electronic device using a thermally conductive sheet containing a resin, a crosslinking agent capable of crosslinking at least a portion of the resin, and a scaly filler, it is possible to provide an electronic device having excellent durability in thermal conductivity by selecting a thermally conductive sheet containing a scaly filler and a resin in a predetermined volume ratio, in which boron nitride is oriented at a predetermined orientation angle, and by heating the thermally conductive sheet while being interposed between a heat sink and a heat generating body, crosslinking at least a portion of the resin with the crosslinking agent, while applying pressure in the thickness direction of the thermally conductive sheet to bond the heat sink and the heat generating body via the thermally conductive sheet, thereby completing the present invention.
[0010] That is, the present invention aims to advantageously solve the above problems, and [1] the manufacturing method of the electronic device of the present invention is a manufacturing method of an electronic device using a thermally conductive sheet containing a resin, a scaly filler, and a crosslinking agent capable of crosslinking at least a part of the resin, wherein the scaly filler is oriented at an orientation angle of 60° to 90° with respect to the main surface of the thermally conductive sheet, and the volume fraction of the scaly filler in the total volume of the resin and the scaly filler is 50 volume% or more, and the thermally conductive sheet is interposed between a heat sink and a heat generating body, and the thermally conductive sheet is heated to crosslink at least a part of the resin with the crosslinking agent, while applying pressure in the thickness direction of the thermally conductive sheet to bond the heat sink and the heat generating body via the thermally conductive sheet. According to the manufacturing method of the electronic device of the present invention, an electronic device having excellent durability in thermal conductivity can be provided. In this specification, the orientation angle of the scaly filler can be measured by the method described in the examples of this specification.
[0011] [2] Here, in the method for manufacturing an electronic device according to [1] above, the pressure applied in the bonding step in the thickness direction of the thermally conductive sheet is preferably 0.1 MPa to 2.0 MPa. If the pressure in the bonding step is within the above range, it is possible to improve the balance between the adhesive strength and thermal conductivity between the heat generating body and the heat sink in the semiconductor device.
[0012] [3] In the method for producing an electronic device according to the above [1] or [2], the resin preferably contains any one of an acrylic polymer, an acrylonitrile-butadiene copolymer, and a styrene-butadiene copolymer. If the thermally conductive sheet constituting the electronic device contains any one of the above polymers, the durability of the thermal conductivity can be further improved.
[0013] [4] In the method for producing an electronic device according to the above [1] to [4], in the bonding step, the thermally conductive sheet preferably has a peel strength of 0.6 N / mm or more when the thermally conductive sheet is heated to 170°C and pressed in the thickness direction at a pressure of 0.6 MPa for 2 hours. If the peel strength of the thermally conductive sheet is equal to or greater than the lower limit, the electronic device has even more excellent durability of thermal conductivity. The peel strength can be measured according to the method described in the Examples of this specification.
[0014] [5] The present invention also aims to advantageously solve the above-mentioned problems, and the thermally conductive sheet of the present invention is a thermally conductive sheet for bonding a heat sink and a heat generating body by heating and pressurizing the heat sink and the heat generating body while the heat sink and the heat generating body are placed between each other, the heat conductive sheet comprising a resin, a scaly filler, and a crosslinking agent capable of crosslinking with at least a portion of the resin, the scaly filler being oriented at an orientation angle of 60° or more and 90° or less with respect to the main surface of the heat conductive sheet, and the volume fraction of the scaly filler being 50 volume% or more of the total volume of the resin and the scaly filler. By applying heat and pressure to such a thermally conductive sheet placed between a heat sink and a heat generating body, an electronic device with excellent durability in thermal conductivity can be obtained. Effect of the Invention
[0015] According to the present invention, it is possible to provide an electronic device having excellent durability in thermal conductivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention will be described in detail. The electronic device of the present invention can be efficiently manufactured by using the thermally conductive sheet of the present invention. The electronic device of the present invention has a structure in which a heat generating body and a heat sink are bonded to each other via the thermally conductive sheet interposed between them.
[0017] (Thermal Conduction Sheet) The thermally conductive sheet of the present invention is a thermally conductive sheet for bonding a heat sink and a heat generating body by heating and pressurizing the heat sink and the heat generating body while being disposed between the heat sink and the heat generating body, and contains a resin, a scaly filler, and a crosslinking agent. The crosslinking agent is capable of crosslinking with at least a part of the resin. The thermally conductive sheet of the present invention may further contain optional components (other components) other than the resin and the scaly filler. The scaly filler contained in the thermally conductive sheet is oriented at an orientation angle of 60° or more and 90° or less with respect to the main surface of the thermally conductive sheet. Furthermore, in the thermally conductive sheet, the volume fraction of the scaly filler in the total volume of the resin and the scaly filler is 50 volume% or more.
[0018] The thermal conductive sheet of the present invention contains a resin, a scaly filler of a predetermined volume fraction, and a crosslinking agent capable of crosslinking at least a part of the resin, and since the scaly filler has an oriented structure, it is presumed that when the thermal conductive sheet is placed between a heat sink and a heat generating body and heated and pressurized to bond the heat sink and the heat generating body, a crosslinking reaction proceeds in at least a part of the resin at the same time as bonding, and further, chemical bonds may occur at the interface with at least one of the heat generating body and the heat dissipating body. As a result, it is presumed that even when the thermal conductive sheet is exposed to the expansion and contraction of the heat generating body and the heat dissipating body, the oriented structure of the scaly filler is well maintained inside the thermal conductive sheet, and the strong adhesion to the heat generating body and the heat dissipating body allows the thermal conductive sheet to follow the expansion and contraction well.
[0019] <Resin> The heat conductive sheet of the present invention contains a resin, so that the heat generating body and the heat dissipating body can be well adhered to each other via the heat conductive sheet. In this specification, rubber and elastomer are included in the "resin". The resin that can be contained in the thermally conductive sheet of the present invention constitutes a matrix resin and also functions as a binder that binds the scaly filler. The resin contained in the thermal conductive sheet of the present invention may contain a crosslinkable resin and, optionally, a resin other than the crosslinkable resin (another resin).
[0020] <<Crosslinkable resin>> The resin contained in the thermal conductive sheet of the present invention may contain a crosslinkable resin. The crosslinkable resin may be crosslinked by a crosslinking agent to become a crosslinked resin. If the resin contains a crosslinkable resin, the crosslinked resin is crosslinked during the manufacture of the electronic device to become a crosslinked resin, which exhibits appropriate strength and elasticity, and thus the thermal conductive durability of the obtained electronic device can be imparted.
[0021] Here, the crosslinkable resin is preferably a resin that is solid at room temperature and normal pressure. In this specification, "room temperature" refers to 23° C., and "normal pressure" refers to 1 atm (absolute pressure).
[0022] The crosslinkable resin can be crosslinked by a crosslinking agent, and in the crosslinking reaction, a crosslinking accelerator can be used as desired. The crosslinking reaction is not particularly limited, and for example, hexamethylenediamine carbamate as an amine-based crosslinking agent or sulfur can be used.
[0023] [Crosslinkable resin] The crosslinkable resin is not particularly limited, and although it depends on the types of the crosslinking agent and the crosslinking accelerator, for example, a resin that is solid at room temperature and normal pressure can be used. Note that the crosslinkable resin is preferably one that does not contain an epoxy group, in other words, a resin other than an epoxy resin, in order to avoid excessive hardness and loss of elasticity.
[0024] - A resin that is solid at room temperature and pressure - Examples of resins that are solid under normal temperature and pressure include acrylic polymers such as poly(2-ethylhexyl acrylate), copolymers of acrylic acid and 2-ethylhexyl acrylate, polymethacrylic acid or its ester, and polyacrylic acid or its ester; styrene-acrylonitrile copolymers; acrylonitrile-butadiene-styrene copolymers (ABS resins); styrene-butadiene copolymers or their hydrogenated products; acrylonitrile-butadiene copolymers (nitrile rubber); styrene-butadiene block copolymers or their hydrogenated products; styrene-isoprene block copolymers or their hydrogenated products; silicone resins such as polyimide silicone resins; fluororesins such as vinylidene fluoride-based fluororesins, tetrafluoroethylene-propylene-based fluororesins, and tetrafluoroethylene-purofluorovinyl ether-based fluororesins. These may be used alone or in combination of two or more. Among these, it is preferable to include at least one of acrylic polymers, acrylonitrile-butadiene copolymers, and styrene-butadiene copolymers.
[0025] The crosslinkable resin preferably has a glass transition temperature of -50.0°C or higher, more preferably -35.0°C or higher, even more preferably -30.0°C or higher, and preferably -8.0°C or lower, more preferably -15.0°C or lower, and even more preferably -20.0°C or lower. If the glass transition temperature of the resin used as the crosslinkable resin is equal to or higher than the above lower limit, the restorability of the obtained thermal conductive sheet can be further improved, and as a result, the durability of the thermal conductivity in the electronic device can be further improved. If the glass transition temperature of the resin used as the crosslinkable resin is equal to or lower than the above upper limit, the obtained thermal conductive sheet can be given appropriate flexibility, and as a result, the durability of the thermal conductivity in the electronic device can be further improved.
[0026] <<Other resins>> The resin other than the crosslinkable resin is not particularly limited, but includes a resin that does not undergo a crosslinking reaction with the crosslinking agent and crosslinking accelerator that contribute to the crosslinking of the crosslinkable resin. For example, a liquid resin that is liquid at room temperature and normal pressure can be used as such a resin. For example, a thermoplastic resin that is liquid at room temperature and normal pressure can be used as the liquid resin. And, for example, the other resin includes an acrylic resin, an epoxy resin, a silicone resin, a fluororesin, an acrylonitrile-butadiene copolymer, and polybutene, which are compounds different from the above-mentioned crosslinkable resin and are liquid thermoplastic resins at room temperature and normal pressure.
[0027] [Crosslinking Agent] The crosslinking agent is not particularly limited as long as it can undergo a crosslinking reaction with the above-mentioned crosslinkable resin, and is not limited as long as it can be used as a crosslinking agent for the resin. Representative crosslinking agents include sulfur-based crosslinking agents, peroxides, and amine-based crosslinking agents that crosslink the unsaturated bonds contained in the resin. These may be used alone or in combination of two or more types in any ratio. Among these, when the crosslinkable resin is an acrylic polymer, it is preferable to use an amine-based crosslinking agent, and when the crosslinkable resin is at least one of an acrylonitrile-butadiene copolymer and a styrene-butadiene copolymer, it is preferable to use a sulfur-based crosslinking agent.
[0028] The amount of the crosslinking agent is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, even more preferably 0.3 parts by mass or more, and preferably 5.0 parts by mass or less, and more preferably 2.5 parts by mass or less, relative to 100 parts by mass of the crosslinkable resin. If the amount of the crosslinking agent is within the above range, the crosslinked resin formed is sufficiently crosslinked by the crosslinking agent, and it is considered that the orientation structure of the scaly filler is well maintained inside the heat conductive sheet by imparting appropriate strength and elasticity to the heat conductive sheet, and the heat conductive sheet can well follow the expansion and contraction of the components in the electronic device.
[0029] [Crosslinking Accelerator] The crosslinking accelerator that can be used in the crosslinking reaction between the crosslinkable resin and the crosslinking agent is not particularly limited, and a sulfenamide crosslinking accelerator can be used. These may be used alone or in combination of two or more in any ratio. Among them, the sulfenamide crosslinking accelerator is preferred.
[0030] The amount of the crosslinking accelerator is preferably 0.5 parts by mass or more, more preferably 0.7 parts by mass or more, even more preferably 1.0 parts by mass or more, and preferably 5.0 parts by mass or less, and more preferably 4.0 parts by mass or less, relative to 100 parts by mass of the crosslinkable resin. If the amount of the crosslinking accelerator is within the above range, the crosslinked resin formed is sufficiently crosslinked by the crosslinking agent, and it is considered that the thermal conductive sheet is provided with appropriate strength and elasticity, thereby maintaining the orientation structure of the scaly filler well inside the thermal conductive sheet and enabling the thermal conductive sheet to well follow the expansion and contraction of the member to which the thermal conductive sheet is applied in the electronic device.
[0031] [Content of crosslinkable resin] The proportion of the crosslinkable resin contained in the thermal conductive sheet must be 50% by volume or less, preferably 10% by volume or more, more preferably 15% by volume or more, even more preferably 30% by volume or more, and particularly preferably 40% by volume or more, based on the total volume of the resin and scaly filler contained in the thermal conductive sheet. If the proportion of the crosslinkable resin based on the total volume of the resin and scaly filler contained in the thermal conductive sheet is equal to or greater than the above lower limit, the thermal conductive sheet will have even more excellent durability in thermal conductivity. The amount of the cross-linkable resin contained in the thermally conductive sheet usually coincides with the amount of the cross-linkable resin used in the production of the thermally conductive sheet.
[0032] [Content of other resins] The proportion of other resins contained in the thermal conductive sheet is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 15% by mass or less, based on the total mass of the resin and scaly filler contained in the thermal conductive sheet. The thermal conductive sheet may not contain other resins. If the proportion of other resins contained in the thermal conductive sheet is equal to or less than the above upper limit, the thermal conductive sheet has even better durability in thermal conductivity.
[0033] <Flake-like filler> Examples of the scaly filler include scaly graphite, scaly boron nitride, scaly alumina, and scaly aluminum nitride. Among them, scaly boron nitride is preferred. The volume average particle diameter of the scaly filler is preferably 10 μm or more, preferably 20 μm or more, more preferably 30 μm or more, preferably 180 μm or less, more preferably 160 μm or less, and even more preferably 140 μm or less. If the volume average particle diameter of the scaly filler is equal to or greater than the above lower limit, it is presumed that the heat transfer path of the scaly filler can be well formed in the heat conductive sheet, and the thermal conductivity of the electronic device can be improved. On the other hand, if the volume average particle diameter of the scaly filler is equal to or less than the above upper limit, the thickness precision of the heat conductive sheet can be sufficiently high. If the volume average particle diameter of the scaly filler is within the above-mentioned predetermined range, the durability of the thermal conductivity of the electronic device can be further improved. In the present invention, the "volume average particle size" can be measured in accordance with JIS Z8825, and refers to the particle size at which the cumulative volume calculated from the small diameter side is 50% in the particle size distribution (volume basis) measured by a laser diffraction method.
[0034] The aspect ratio (major axis / minor axis) of the scaly filler is preferably more than 1 and not more than 10, more preferably more than 1 and not more than 5. When the aspect ratio of the scaly filler is more than 1 and not more than 10, it is presumed that the scaly filler is easily well oriented in the thickness direction in the thermal conductive sheet, and the thermal conductivity in the thickness direction of the thermal conductive sheet can be improved. In the present invention, the "aspect ratio" can be determined by observing the scaly filler with a SEM (scanning electron microscope), measuring the maximum diameter (long diameter) and the particle diameter (short diameter) in a direction perpendicular to the maximum diameter for any 50 scaly fillers, and calculating the average ratio of the long diameter to the short diameter (long diameter / short diameter). In the above, the "long diameter" refers to the length in the direction of the long axis of the main surface of the scaly shape, and the "short diameter" refers to the length in the direction perpendicular to the long axis of the main surface.
[0035] <<Content of scale-like filler>> The content of the scaly filler in the thermal conductive sheet must be 50% by volume or more, more preferably 60% by volume or more, and preferably 70% by volume or less, based on the total of the resin and the scaly filler. If the content of the scaly filler in the thermal conductive sheet is equal to or more than the lower limit, the insulation breakdown resistance of the thermal conductive sheet can be improved, and the thermal conductivity itself and the durability of the thermal conductivity can be further improved. In addition, if the content of the scaly filler in the thermal conductive sheet is equal to or less than the upper limit, the thermal conductive sheet can be effectively prevented from separating into strips due to pressure or the like, particularly in the case where the thermal conductive sheet has a structure in which strips are joined in parallel to each other, and the integrity of the thermal conductive sheet can be improved.
[0036] <Other ingredients> The thermally conductive sheet of the present invention may further include, as desired, components other than the above-mentioned resin, crosslinking agent, and scaly filler (hereinafter, sometimes referred to as "other components"). The other components are not particularly limited as long as they are components that can be used in the manufacture of a thermally conductive sheet, and examples of the other components include fibrous carbon materials; flame retardants such as red phosphorus flame retardants and phosphate ester flame retardants; plasticizers such as fatty acid ester plasticizers; toughness improvers such as urethane acrylate; moisture absorbents such as calcium oxide and magnesium oxide; adhesion improvers such as silane coupling agents, titanium coupling agents, and acid anhydrides; wettability improvers such as nonionic surfactants and fluorine-based surfactants; ion trapping agents such as inorganic ion exchangers; and anti-aging agents.
[0037] <Thermal Conduction Sheet Structure> The thermal conductive sheet of the present invention has a structure in which the above-mentioned scaly filler is oriented at an orientation angle of 60° to 90° with respect to the main surface of the thermal conductive sheet. If the scaly filler is oriented in the thickness direction of the thermal conductive sheet, the thermal conductivity of the thermal conductive sheet in the thickness direction can be improved.
[0038] The orientation angle of the scaly filler is preferably 70° or more, more preferably 75° or more, and even more preferably 78° or more. When the orientation angle of the scaly filler is equal to or more than the lower limit, the thermal conductivity of the thermal conductive sheet can be improved.
[0039] <Thermal Conduction Sheet Properties> <<Thermal conductivity>> The thermal conductivity of the thermal conductive sheet in the thickness direction is preferably 15 W / m K or more, and more preferably 20 W / m K or more. The upper limit of the thermal conductivity of the thermal conductive sheet in the thickness direction is not particularly limited, but is, for example, 45 W / m K or less. The thermal conductivity of the thermal conductive sheet in the thickness direction can be adjusted by the types and proportions of materials and components contained in the thermal conductive sheet, as well as the manufacturing method and manufacturing conditions of the thermal conductive sheet.
[0040] <Thickness of thermal conductive sheet> The thickness of the thermal conductive sheet of the present invention is not particularly limited, but is preferably 50 μm or more, more preferably 100 μm or more, more preferably 200 μm or more, and preferably 500 μm or less, more preferably 450 μm or less, and even more preferably 400 μm or less. If the thickness of the thermal conductive sheet is equal to or greater than the above lower limit, the thermal conductive sheet is not excessively thinned, and the strength and insulating properties of the thermal conductive sheet can be improved. If the thickness of the thermal conductive sheet is equal to or less than the above upper limit, the thermal properties of the thermal conductive sheet in the thickness direction can be improved.
[0041] <Method of manufacturing thermal conductive sheets> The thermally conductive sheet of the present invention can be efficiently manufactured by a manufacturing method including: (A) a pre-thermally conductive sheet forming step of pressurizing a composition containing a resin, a scaly filler, and a crosslinking agent capable of crosslinking at least a part of the resin to form a sheet to obtain a pre-thermally conductive sheet; (B) a laminate forming step of stacking a plurality of pre-thermally conductive sheets in the thickness direction or folding or rolling the pre-thermally conductive sheets to obtain a laminate; and (C) a slicing step of slicing the laminate at an angle of 45° or less with respect to the stacking direction to obtain a thermally conductive sheet. The thermally conductive sheet of the present invention may further include any step other than the above steps (A) to (C).
[0042] <(A) Pre-heat conductive sheet molding process> In the pre-thermal conductive sheet molding step, a composition containing a resin, a flaky filler, and a crosslinking agent capable of crosslinking with at least a portion of the resin is pressed into a sheet to obtain a pre-thermal conductive sheet.
[0043] <<Composition>> The composition includes a resin, a scaly filler, and a crosslinking agent capable of crosslinking at least a portion of the resin. The composition may further include a crosslinking accelerator. Furthermore, the composition may further include components (other components) other than the above-mentioned resin, scaly filler, crosslinking agent, and crosslinking accelerator.
[0044] 〔resin〕 Here, the resin contained in the composition contains a crosslinkable resin, and may optionally contain a resin other than the crosslinkable resin. As the crosslinkable resin, for example, the crosslinkable resin that can be used to form the crosslinked resin described above in the section "Thermal Conductive Sheet" can be used in the ratio described above. The blending amount of the crosslinkable resin in the composition corresponds to the blending range described for the "content ratio of the crosslinkable resin" contained in the thermal conductive sheet described above. In addition, as the resin other than the crosslinkable resin, for example, the resin (other resin) other than the crosslinkable resin that can be contained in the resin described above in the section "Thermal Conductive Sheet" can be used in the ratio described above.
[0045] [Scaly filler] As the scaly filler, for example, the scaly filler described above in the section "Thermal Conductive Sheet" can be used in the ratio described above.
[0046] [Crosslinking Agent] As the crosslinking agent, the crosslinking agents described above in the section "Thermal Conductive Sheet" can be used in the proportions described above.
[0047] [Crosslinking Accelerator] As the crosslinking accelerator, those mentioned in the section "Thermal Conductive Sheet" can be used in the proportions mentioned above.
[0048] [Other ingredients] As other components that can be contained in the composition, other components that can be contained in the thermally conductive sheet described above in the section "Thermal Conductive Sheet" can be used.
[0049] [Preparation of Composition] The composition is not particularly limited and can be prepared by mixing the above-mentioned components. The mixing of the above-mentioned components is not particularly limited, and can be performed using known mixing devices such as a kneader; a mixer such as a Henschel mixer, a Hobart mixer, or a high-speed mixer; a twin-screw kneader; or a roll. The mixing may be performed in the presence of a solvent such as ethyl acetate. The resin may be dissolved or dispersed in advance in a solvent to form a resin solution, which may then be mixed with the scaly filler and crosslinking agent, as well as an optionally added crosslinking accelerator and other components. The mixing time may be, for example, 5 minutes or more and 60 minutes or less. The mixing temperature may be, for example, 5°C or more and 150°C or less.
[0050] <<Molding of the composition>> The composition prepared as described above can be optionally degassed and crushed, and then pressed to form into a sheet. The sheet-shaped composition thus pressurized can be used as a pre-heat conductive sheet. If a solvent is used during mixing, it is preferable to remove the solvent before forming into a sheet. For example, if degassing is performed using vacuum degassing, the solvent can be removed at the same time as degassing.
[0051] Here, the composition can be molded into a sheet using a known molding method such as press molding, rolling molding, or extrusion molding, without any particular limitation, as long as the molding method is one in which pressure is applied. Among them, the composition is preferably molded into a sheet by rolling molding (primary processing), and more preferably molded into a sheet by a predetermined roll molding in which the composition is passed between a first roll and a second roll having a faster peripheral speed than the first roll. The peripheral speed ratio of the second roll to the first roll ("peripheral speed of the second roll" / "peripheral speed of the first roll") is preferably 1.03 / 1 or more and 2 / 1 or less. In addition, the distance between the first roll and the second roll can be, for example, 1 mm or more and 3 mm or less.
[0052] <<Pre-heat conductive sheet>> In the pre-thermal conductive sheet obtained by pressing the composition into a sheet, the scale-like filler particles are primarily oriented in the in-plane direction, and it is presumed that this particularly improves the thermal conductivity of the pre-thermal conductive sheet in the in-plane direction.
[0053] <(B) Laminate formation process> In the laminate formation step, a plurality of pre-thermally conductive sheets obtained in the pre-thermally conductive sheet forming step are laminated in the thickness direction, or the pre-thermally conductive sheet is folded or rolled to obtain a laminate in which a plurality of thermally conductive sheets containing resin and scaly filler are formed in the thickness direction. Here, the formation of the laminate by folding the pre-thermally conductive sheet is not particularly limited, and can be performed by folding the pre-thermally conductive sheet at a constant width using a folding machine. In addition, the formation of the laminate by rolling the pre-thermally conductive sheet is not particularly limited, and can be performed by rolling the pre-thermally conductive sheet around an axis parallel to the short side or long side of the pre-thermally conductive sheet. In addition, the formation of the laminate by stacking the pre-thermally conductive sheets is not particularly limited, and can be performed using a lamination device.
[0054] In the lamination process, it is preferable to heat the obtained laminate (hereinafter also referred to as the first laminate) at a temperature lower than the heating temperature in the bonding process described below, while pressing it in the lamination direction (secondary pressing) to form a second laminate.
[0055] Here, the pressure when pressing the laminate in the stacking direction can be 0.05 MPa or more and 0.90 MPa or less. Alternatively, isostatic pressing can be performed using an apparatus such as an autoclave. The pressure of the isostatic pressing is preferably in the range of 0.3 MPa or more and 0.9 MPa or less.
[0056] The heating temperature of the laminate is not particularly limited as long as it is lower than the heating temperature in the bonding step described below, but can be less than 90°C, preferably 85°C or less, and more preferably 80°C or less, and can be 30°C or more, preferably 40°C or more, and more preferably 50°C or more. Furthermore, the heating time for the laminate can be, for example, from 10 seconds to 60 minutes.
[0057] In addition, in the laminate obtained by stacking, folding or rolling the pre-thermal conductive sheet, it is presumed that the scaly filler is oriented in a direction approximately perpendicular to the stacking direction.
[0058] <(C) Slicing process> In the slicing step, the laminate obtained in the laminate forming step is sliced at an angle of 45° or less with respect to the lamination direction to obtain a thermally conductive sheet consisting of slices of the laminate. Here, the method for slicing the laminate is not particularly limited, and examples thereof include a multi-blade method, a laser processing method, a water jet method, and a knife processing method. In addition, the cutting tool used when slicing the laminate is not particularly limited, and a slicing member having a smooth plate surface with slits and a blade portion protruding from the slit portion (for example, a plane or slicer with a sharp blade) can be used.
[0059] From the viewpoint of increasing the thermal conductivity of the thermal conduction sheet, the angle at which the laminate is sliced is preferably 30° or less with respect to the stacking direction, more preferably 15° or less with respect to the stacking direction, and preferably approximately 0° with respect to the stacking direction (i.e., in the direction along the stacking direction).
[0060] In the thermally conductive sheet thus obtained, the scaly filler is oriented at an orientation angle of 60° to 90° with respect to the main surface of the thermally conductive sheet, and the thermal conductivity in the thickness direction is excellent. In addition, since the thermally conductive sheet is heated at a temperature lower than the heating temperature in the bonding step in the manufacturing process, unreacted crosslinking agent remains in the thermally conductive sheet, and by carrying out the bonding step described below, an electronic device with excellent durability in thermal conductivity is obtained.
[0061] (Electronic device manufacturing method) The method for producing an electronic device of the present invention is a method for producing an electronic device using a thermally conductive sheet containing a resin, a scaly filler, and a crosslinking agent capable of crosslinking at least a part of the resin. The thermally conductive sheet is the thermally conductive sheet of the present invention described above, in which the scaly filler is oriented at an orientation angle of 60° to 90° with respect to the main surface, and the volume fraction of the scaly filler in the total volume of the resin and the scaly filler is 50% by volume or more. The method includes a bonding step of heating the thermally conductive sheet with the thermally conductive sheet interposed between a heat sink and a heat generating body, crosslinking at least a part of the resin with the crosslinking agent, and applying pressure in the thickness direction of the thermally conductive sheet to bond the heat sink and the heat generating body via the thermally conductive sheet. According to the method for producing an electronic device, an electronic device having excellent durability in thermal conductivity can be produced.
[0062] <Thermal Conduction Sheet> As the thermally conductive sheet, the above-mentioned thermally conductive sheet of the present invention is used.
[0063] <Heater> The heat generating body is an object to which a heat sink is bonded via a thermally conductive sheet to dissipate heat. Examples of the heat generating body include semiconductor chips, semiconductor packages, automotive power modules, displays, and industrial power modules.
[0064] <Heat sink> The heat sink is a member that dissipates heat from a heat generating body via a thermally conductive sheet. Examples of the heat sink include a heat spreader, a heat sink, and a water-cooled pipe.
[0065] <Adhesion process> In the bonding process, the heat conductive sheet is heated while being interposed between the heat sink and the heat generating body, and at least a part of the resin is crosslinked by the crosslinking agent, while pressure is applied in the thickness direction of the heat conductive sheet to bond the heat sink and the heat generating body via the heat conductive sheet. This is presumably because at least a part of the resin and the crosslinking agent undergo a crosslinking reaction to form a crosslinked resin, and chemical bonds may occur at the interface between the heat generating body and the heat conductive sheet, and at the interface between the heat sink and the heat conductive sheet, and the heat conductive sheet may be firmly bonded to the heat conductive sheet and the heat generating body and the heat sink. Furthermore, the formed crosslinked resin also improves the sheet strength of the heat conductive sheet, and as a result, the durability of the thermal conductivity in the electronic device can be improved.
[0066] Here, the pressure when the thermally conductive sheet is pressed in the thickness direction in the bonding process is preferably 0.1 MPa or more, more preferably 0.2 MPa or more, even more preferably 0.6 MPa or more, preferably 2.0 MPa or less, and more preferably 1.5 MPa or less. If the pressure when the thermally conductive sheet is pressed in the thickness direction is equal to or higher than the above lower limit, the heat generating body and the heat dissipating body can be firmly bonded via the thermally conductive sheet in the bonding process. On the other hand, if the pressure when the thermally conductive sheet is pressed in the thickness direction is equal to or lower than the above upper limit, the thermally conductive sheet is excessively crushed, the orientation structure of the scale-like filler collapses, and the thermal conductivity is effectively prevented from decreasing.
[0067] The heating temperature in the adhesion process is not particularly limited, but is preferably over 90 ° C, more preferably 100 ° C or more, even more preferably 155 ° C or more, preferably 200 ° C or less, and more preferably 190 ° C or less. If the heating temperature in the adhesion process is above the lower limit, the crosslinking reaction proceeds well, and it is presumed that the chemical bond at the interface between the heat generating body / heat dissipating body and the thermal conductive sheet can be well formed. The adhesive strength of the heat generating body and the heat dissipating body is increased, and the sheet strength of the thermal conductive sheet is also increased, so that the durability of the thermal conductivity of the electronic device can be further improved. If the heating temperature in the adhesion process is below the upper limit, the deterioration of the resin constituting the thermal conductive sheet can be suppressed, and the durability of the thermal conductivity can be further improved.
[0068] The heating time in the adhesion process is not particularly limited, but may be, for example, 1 hour or more and 8 hours or less. It is presumed that if the heating time in the adhesion process is equal to or more than the lower limit, the crosslinking reaction proceeds well, and the chemical bond at the interface between the heat generating body / heat dissipating body and the thermal conductive sheet can be formed well. The adhesive strength of the heat generating body and the heat dissipating body is increased, and the sheet strength of the thermal conductive sheet is also increased, so that the durability of the thermal conductivity of the electronic device can be further improved. On the other hand, if the heating time in the adhesion process is equal to or less than the upper limit, the crosslinking reaction is prevented from proceeding excessively, and the flexibility of the thermal conductive sheet can be well maintained, and as a result, the durability of the thermal conductivity of the thermal conductive sheet can be further improved.
[0069] Even in the thermally conductive sheet that has undergone the above-mentioned bonding process, the scaly filler is oriented at an angle of 60° to 90° relative to the main surface of the thermally conductive sheet, resulting in excellent thermal conductivity. Furthermore, as a result of the cross-linking reaction that has progressed in the bonding process, the thermally conductive sheet itself is endowed with mechanical strength, and the oriented structure of the boron nitride is also strengthened, resulting in excellent durability of thermal conductivity.
[0070] The heating in the bonding step may be performed by heat generation from a heating element, and the pressure in the bonding step may be applied by the weight of the heating element or heat dissipating element.
[0071] When the bonding step is performed under conditions in which the thermally conductive sheet is heated to 170° C. and pressed in the thickness direction at a pressure of 0.6 MPa for 2 hours, the peel strength of the thermally conductive sheet is preferably 0.6 N / mm or more, more preferably 0.8 N / mm or more, and even more preferably 1.2 N / mm or more. The peel strength is measured according to the method described in the Examples below. EXAMPLES
[0072] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples. In the following description, "%" and "parts" expressing amounts are based on mass unless otherwise specified. In each example and each comparative example, various attributes were measured or evaluated by the following methods.
[0073] <Orientation angle of boron nitride> The orientation angle was measured using the thermally conductive sheets prepared in the Examples and Comparative Examples and two test structures prepared for each Example and Comparative Example in the same manner as in the <peel strength> test described below. The test structures were prepared by heating the thermally conductive sheets at 170°C for two hours while applying a pressure of 0.6 MPa or 2.0 MPa to the thermally conductive sheets, and bonding the copper foil and the thermally conductive sheets, in the same manner as in the <peel strength> test. The orientation angle of boron nitride in the thermally conductive sheets prepared in the Examples and Comparative Examples and in the structures prepared as described above was determined by observing the cross section of the thermally conductive sheet / structure cut into a regular octagon with a scanning electron microscope (SEM, Hitachi High-Technologies Corporation, "SU-3500") at a magnification that fits the top to bottom of the sheet. The magnification was 700x. Specifically, 50 lines were drawn along the long axis of boron nitride in the cross section, and the average angle of the long axis with respect to the surface of the thermally conductive sheet was calculated. If the angle was 90° or more, the supplementary angle was used. This was performed for eight faces, and the largest value among the eight faces was taken as the orientation angle of boron nitride in the thermally conductive sheet.
[0074] <Thermal conductivity> [Thermal diffusivity in the thickness direction α] The thermal diffusivity of the thermal conductive sheet was measured using a thermal diffusivity / thermal conductivity measuring device (ai-Phase Mobile 1u, manufactured by Ai-Phase Corporation) in accordance with the provisions of ISO22007-3. [Specific heat at constant pressure Cp] The specific heat was measured at 25° C. under a temperature increase rate of 10° C. / min using a differential scanning calorimeter (manufactured by Rigaku, product name "DSC8230"). [Specific gravity ρ (density)] The measurement was performed using an automatic specific gravity meter (manufactured by Toyo Seiki Co., Ltd., product name "DENSIMETER-H"). Then, each measured value is calculated using the following formula (I): λ = α × Cp × ρ (I) The thermal conductivity λ (W / m K) in the thickness direction of the thermal conductive sheet at 25°C was calculated by substituting
[0075] <Voltage test value> The withstand voltage test values of the thermally conductive sheets produced in the examples and comparative examples were measured using an in-oil test device (manufactured by Tama Densoku Co., Ltd., product name "TJ-20S"). Specifically, a thermally conductive sheet cut into a roughly 3 cm square was used as a sample, and the sample was immersed in silicone oil at 23°C. One minute after immersion, voltage application was started at a voltage increase rate of 0.6 kV / sec, and the voltage (kV) was measured when the current (detection current) flowing through the sample reached 10 mA. The obtained voltage (kV) value was divided by the thickness (mm) of the thermally conductive sheet sample to obtain a voltage resistance test value (kV / mm). A higher voltage resistance test value indicates that the thermally conductive sheet has better resistance to dielectric breakdown.
[0076] <Peel strength> The adhesion between the thermal conductive sheet and the metal plate was measured using a peel analysis device (Kyowa Interface Science Co., Ltd., "VPA-H100"). First, a thermally conductive sheet of 40 (mm) x 40 (mm) x 0.3 (mm) was sandwiched between copper foil of the same size on both sides, and then sandwiched between a copper plate of 50 (mm) x 50 (mm) x 10 (mm) and an aluminum plate of 50 x 50 x 10 mm, and the four corners were fixed with screws to prepare a copper plate-copper foil-thermally conductive sheet-copper foil-aluminum plate structure. Two such structures were prepared for each of the examples and comparative examples. Note that such structures are simulated reproductions of electronic devices. By adjusting the screws at the four corners, the thermally conductive sheet was heated at 170°C for two hours under a pressure of 0.6 MPa or 2.0 MPa to bond the copper foil and the thermally conductive sheet. The thermally conductive sheet with copper foil on both sides was taken out of the structure, cut into a lengthwise direction of 40 (mm) x width 10 (mm) x thickness 0.3 (mm), and then the thermally conductive sheet was fixed on a flat table. Next, a part of the copper foil located on the main surface side of the thermal conductive sheet was peeled off at one end of the thermal conductive sheet. The copper foil of the peeled off portion was then held and peeled off at a speed of 200 mm / min in a 90° direction in an atmosphere of 25°C. The maximum tensile strength measured when the copper foil was peeled off was recorded as the peel strength (N), and the value obtained by dividing the peel strength by the width was recorded as the peel strength (N / mm).
[0077] <Durability of thermal conductivity> A test piece measuring 25 mm x 25 mm x 0.30 mm was cut out from the thermally conductive sheets produced in the Examples and Comparative Examples. The test piece obtained was sandwiched between a copper plate measuring 50 mm x 50 mm x 8 mm and an aluminum plate of the same size, and the four corners were secured with screws to produce a copper plate-thermally conductive sheet-aluminum plate structure. This structure is a simulated reproduction of an electronic device. The structure was created so that a pressure of 0.6 MPa was applied to the sheet by adjusting the screws at the four corners, and this structure was kept at 175°C for 24 hours. After that, the structure was cooled to room temperature, and the pressure of the screws was adjusted to 0.3 MPa and it was kept in an atmosphere of 175°C for another 24 hours, which constituted one cycle. Here, the 8 mm thick copper and aluminum plates do not normally deform significantly, but by changing the pressure applied to the structure, the thermal expansion in the operating environment of an electronic device was reproduced in a pseudo manner. The test pieces used in the above tests were evaluated using a transient thermal resistance measuring device (manufactured by Siemens, product name "T3Ster") to evaluate the thermal resistance of the copper plate-thermal conductive sheet-aluminum plate structure, and the thermal resistance of the initial structure was compared with that of the structure after 20 cycles. The higher the thermal conductivity retention rate (%) calculated according to the formula below, the more excellent the durability of the thermal conductivity of the electronic device. Incidentally, the thermal conductive sheet was an uncrosslinked sheet sandwiched between the structures, but the crosslinking reaction proceeded at a temperature of 175°C during the durability test. (Thermal resistance maintenance rate%) = 100 x {1 - (thermal resistance after 20 cycles - initial thermal resistance) ÷ initial thermal resistance}
[0078] Example 1 <Preparation of Composition> As the crosslinkable resin, an acrylic rubber, which is an acrylic resin that is solid at room temperature and normal pressure (manufactured by Zeon Corporation, product name "Nipol (registered trademark) AR-12", glass transition temperature: -30.3°C, specific gravity: 1.1 g / cm 3 210 parts of hexagonal boron nitride (h-BN) (manufactured by Dandong Chemical Engineering, product name "HSL-HP50", aspect ratio: 1.5, specific gravity: 2.23) as a scaly filler were kneaded for 20 minutes at a temperature of 120°C using a pressure kneader (manufactured by Nippon Spindle) to obtain a composition. 3.2 parts of Nocrac 224 as an anti-aging agent, 1.05 parts of Diak#1 (manufactured by Chemours) as a crosslinking agent, and 4.2 parts of Noccela DT as a crosslinking accelerator were added to the obtained composition, and the mixture was kneaded for 5 minutes at a temperature of 80°C to obtain a composition.
[0079] <Pre-heat conductive sheet forming process> Next, 500 g of the obtained composition was rolled into a sheet using a first roll and a second roll under the following conditions: a gap between the first roll and the second roll of 1 mm, a roll temperature of 25° C., a sheet discharge speed (peripheral speed of the first roll) of 2 m / min, and a peripheral speed ratio of the second roll to the first roll (second roll / first roll): 1.15 / 1. The rolling process was repeated while keeping the sheet conveying direction the same. The rolling process was performed 10 times in total to obtain a pre-heat-conductive sheet having a thickness of 1 mm.
[0080] <First laminate formation process> Next, the obtained pre-thermal conductive sheet was cut into a size of 50 mm length×50 mm width, and 50 sheets were stacked in the thickness direction to obtain a first stack having a height of about 50 mm.
[0081] <Second laminate formation process> The obtained first laminate was wrapped in release PET (polyethylene terephthalate), taped, and vacuum-packaged in a PET retort package. This was heated and pressurized for 30 minutes in an autoclave (Hanyu Iron Works, small autoclave "DANDELION") at a temperature of 80°C and a pressure of 0.8 MPa (absolute pressure) from all directions to obtain a second laminate.
[0082] <Slicing process> Next, while pressing the laminated surface of the secondary pressurized laminate with a pressure of 0.3 MPa, a wood slicer (Marunaka Iron Works, product name "Super Finish Planer Super Mecha S") was used to slice at an angle of 0 degrees to the lamination direction (in other words, in the normal direction of the main surface of the laminated primary sheets) to obtain a secondary sheet (thermal conductive sheet) of length 50 mm x width 50 mm x thickness 0.30 mm. The thermal conductive sheet is composed of strips joined in parallel in a direction perpendicular to the thickness direction of the thermal conductive sheet (a direction at an angle of 90° to the thickness direction). The width of the strips in this approximately perpendicular direction is approximately the same as the thickness of the pre-thermal conductive sheet. The thermally conductive sheet thus obtained was subjected to various measurements and evaluations as described above. The results are shown in Table 1.
[0083] (Examples 2 and 3) In <Preparation of Composition>, the same operations, measurements, and evaluations as in Example 1 were carried out, except that the amounts of the various components were changed as shown in Table 1. The results are shown in Table 1.
[0084] Example 4 The crosslinkable resin to be blended was an acrylic rubber (manufactured by Zeon Corporation, product name "Nipol (registered trademark) AR-14", glass transition temperature: -42.0°C, specific gravity: 1.1 g / cm) which is a solid acrylic resin at room temperature and normal pressure. 3 ) was used. Except for this, the same operations, measurements, and evaluations as in Example 2 were carried out. The results are shown in Table 1.
[0085] Example 5 The blending amount of the acrylic resin was 75 parts, and the other resin that was not a crosslinkable resin was liquid nitrile butadiene rubber (hereinafter also referred to as "liquid NBR") (Nipol 1312, manufactured by Nippon Zeon, specific gravity: 1 g / cm 3 ) was blended in at 75 parts (12% by mass based on the total mass of the crosslinkable resin, other resins, and scaly filler), and the blending amount of the scaly filler was 480 parts. Other components (antiaging agent, crosslinking agent, and crosslinking accelerator) were also changed as shown in Table 1. Since liquid NBR does not react with Diak#1 blended as a crosslinking agent for the acrylic rubbers AR-12 and AR-14, it essentially plays a role like a plasticizer. Other than the above, various operations, measurements, and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 1.
[0086] Example 6 The blending ratio of acrylic resin was 43 parts, and liquid NBR (Nipol 1312, manufactured by Zeon Corporation, specific gravity: 1 g / cm) was used as other resin that is not a cross-linking resin. 3) was 100 parts (17% by mass based on the total mass of the crosslinkable resin, other resins, and scaly filler), and the amount of the scaly filler was 460 parts. Other components (antiaging agent, crosslinking agent, and crosslinking accelerator) were also changed as shown in Table 1. Since liquid NBR does not react with Diak#1, which is mixed as a crosslinking agent for the acrylic rubbers AR-12 and AR-14, it essentially plays a role like a plasticizer. Other than the above, various operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0087] Example 7 As the crosslinkable resin, solid nitrile butadiene rubber (hereinafter also referred to as "solid NBR") (Nipol3350: manufactured by Nippon Zeon Co., Ltd., Mooney viscosity: 50, glass transition temperature: -38.0°C, specific gravity: 1 g / cm 3 ) was used in an amount of 180 parts. The amount of the scaly filler was 590 parts, and Nocrac 224 as an anti-aging agent was 2.7 parts. Furthermore, 5.4 parts of zinc oxide as a vulcanization activator, 1.8 parts of stearic acid as a vulcanization activator, 2.7 parts of sulfur (Kinkaji Fine Sulfur 325 Mesh: manufactured by Tsurumi Chemical Industry Co., Ltd.) as a sulfur-based crosslinking agent, and 3.6 parts of Noccela CZ-G as a crosslinking accelerator were mixed. Except for the above points, various operations, measurements, and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 1.
[0088] Example 8 As the crosslinkable resin, a styrene butadiene rubber (hereinafter also referred to as "solid SBR") that is solid at room temperature and normal pressure (Nipole 1502, manufactured by Nippon Zeon Co., Ltd., glass transition temperature: -50.0°C, specific gravity: 0.94 g / cm) was used. 3) was used. The amount of the scaly filler was 630 parts, and Nocrac 224 as an anti-aging agent was 2.7 parts. Furthermore, 5.4 parts of zinc oxide as a vulcanization activator, 1.8 parts of stearic acid as a vulcanization activator, 2.7 parts of sulfur (Kinkaji Fine Sulfur 325 Mesh: manufactured by Tsurumi Chemical Industry Co., Ltd.) as a sulfur-based crosslinking agent, and 3.6 parts of Noccela CZ-G as a crosslinking accelerator were mixed. Except for the above points, various operations, measurements, and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 1.
[0089] Comparative Example 1 Except for not adding the crosslinking agent and the crosslinking accelerator, the same operations, measurements, and evaluations were carried out as in Example 2. The results are shown in Table 1.
[0090] [Table 1]
[0091] As can be seen from Table 1, when manufacturing electronic devices using a thermally conductive sheet containing resin, scaly filler, and a crosslinking agent capable of crosslinking at least a portion of the resin, a sheet containing scaly filler and resin in a predetermined volume ratio and in which boron nitride is oriented at a predetermined orientation angle within the sheet is selected as the thermally conductive sheet, and the thermally conductive sheet is heated while being interposed between a heat sink and a heat generating body to crosslink at least a portion of the resin with the crosslinking agent, while pressure is applied in the thickness direction of the thermally conductive sheet to bond the heat sink and heat generating body via the thermally conductive sheet, and the electronic devices of Examples 1 to 8 have excellent durability in thermal conductivity. [Industrial Applicability]
[0092] According to the present invention, it is possible to provide an electronic device having excellent durability in thermal conductivity.
Claims
1. A method for producing an electronic device using a thermally conductive sheet containing a resin, a flaky filler, and a crosslinking agent capable of crosslinking with at least a portion of the resin, comprising: In the thermal conductive sheet, the scaly filler is oriented at an orientation angle of 60° or more and 90° or less with respect to a main surface of the thermal conductive sheet, and a volume fraction of the scaly filler in a total volume of the resin and the scaly filler is 50 volume% or more, A method for manufacturing an electronic device, comprising: a bonding step of heating the thermally conductive sheet while the thermally conductive sheet is interposed between a heat sink and a heat generating body, crosslinking at least a portion of the resin with the crosslinking agent, while applying pressure in the thickness direction of the thermally conductive sheet to bond the heat sink and the heat generating body via the thermally conductive sheet.
2. The method for manufacturing an electronic device according to claim 1 , wherein the pressure applied in the bonding step in the thickness direction of the thermal conductive sheet is equal to or greater than 0.1 MPa and equal to or less than 2.0 MPa.
3. 2. The method for producing an electronic device according to claim 1, wherein the resin includes any one of an acrylic polymer, an acrylonitrile-butadiene copolymer, and a styrene-butadiene copolymer.
4. 4. The method for manufacturing an electronic device according to claim 1, wherein in the bonding step, when the thermally conductive sheet is heated to 170° C. and pressed in the thickness direction at a pressure of 0.6 MPa for two hours, the peel strength of the thermally conductive sheet is 0.6 N / mm or more.
5. A thermally conductive sheet for bonding a heat sink and a heat generating body by applying heat and pressure to the heat sink and the heat generating body while being disposed between the heat sink and the heat generating body, the thermally conductive sheet comprising: The composite material includes a resin, a scaly filler, and a crosslinking agent capable of crosslinking with at least a portion of the resin, the scaly filler is oriented at an orientation angle of 60° or more and 90° or less with respect to the main surface of the thermal conductive sheet, A thermally conductive sheet, wherein the volume fraction of the scaly filler is 50 volume % or more of the total volume of the resin and the scaly filler.
Citation Information
Patent Citations
Thermally conductive sheet
JP2018203857A